2019
DOI: 10.1002/jmv.25381
|View full text |Cite
|
Sign up to set email alerts
|

Epstein‐Barr virus LMP2A utilizes Syk and PI3K to activate NF‐κB in B‐cell lymphomas to increase MIP‐1α production

Abstract: The incidence of Hodgkin's lymphoma (HL) is growing due to an increase in Epstein‐Barr virus (EBV)‐associated HL in AIDS patients. The HL tumor microenvironment is vital for the survival of the malignant Hodgkin‐Reed Sternberg (HRS) cells of HL, which express the EBV protein latent membrane protein 2A (LMP2A). While previous work shows that LMP2A mimics B‐cell receptor (BCR) signaling to promote the survival of HRS cells, the ability of LMP2A to establish and maintain the tumor microenvironment through the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 57 publications
(151 reference statements)
0
14
0
Order By: Relevance
“…Luster et al previously highlighted the relationship between chemokines and inflammation, likely explaining their predicted role in psoriasis patients. 40 IRF7, IFIT3, OAS1, GBP1, and ISG15 were also identified as promising targets for the treatment of psoriasis. Raposo et al detected significant upregulation of 16 different antiviral genes in lesional psoriatic skin, with ISG15 expression being increased more than two-fold, 41 and others have similarly observed cutaneous upregulation of antiviral proteins in the context of psoriasis, 42 potentially explaining why these patients rarely experience cutaneous viral infections.…”
Section: Discussionmentioning
confidence: 99%
“…Luster et al previously highlighted the relationship between chemokines and inflammation, likely explaining their predicted role in psoriasis patients. 40 IRF7, IFIT3, OAS1, GBP1, and ISG15 were also identified as promising targets for the treatment of psoriasis. Raposo et al detected significant upregulation of 16 different antiviral genes in lesional psoriatic skin, with ISG15 expression being increased more than two-fold, 41 and others have similarly observed cutaneous upregulation of antiviral proteins in the context of psoriasis, 42 potentially explaining why these patients rarely experience cutaneous viral infections.…”
Section: Discussionmentioning
confidence: 99%
“…The 4 class I PI3K isozymes (PI3Kα, PI3Kβ, PI3Kγ, and PI3Kδ) regulate a variety of cellular functions, and the δ isoform is specifically involved in B-cell signaling and regulates B-cell response to chemokines and cytokines [122,123]. In vitro exposure of HRS cells to a specific inhibitor of PI3Kδ resulted in increased levels of apoptosis [124]. Based on these findings, Idelalisib, a selective inhibitor of PI3Kδ, was administered to patients affected by relapsed/refractory cHL in a phase II study [107]: compared to other B-cell malignancies, the activity of Idelalisib in this patient population was modest, with only a 20% response rate.…”
Section: From Bench To Bedside: Therapeutical Potential Of Tumor-mmentioning
confidence: 99%
“… 14 Previous studies have shown that patients with chronic prostatitis have higher concentrations of MIP-2 and MIP-1α in their prostatic fluid, and that the levels of these cytokines are positively correlated with the severity of chronic prostatitis. 15 This study noted that combination therapy with tamsulosin hydrochloride and terazosin decreased IL-2, PGE-2, MIP-1α, and MIP-2 levels. This indicates that this therapeutic approach inhibited patient inflammatory responses.…”
Section: Discussionmentioning
confidence: 70%